Development of chitosan/alginate/silver nanoparticles hydrogel scaffold for soft tissue engineering applications - Ramli, Roslinda Hani (2017)
A biodegradable scaffold in tissue engineering serves as a temporary skeleton to accommodate and stimulate new tissue growth. Alginate (Alg) and chitosan (Chi) are both popular materials applied as biomaterials or bioimplants. However, Alg derived from brown algae is highly compliant and easily decomposed in fluid, whilst Chi derived from shrimp shells has weak strength. In rectify these problems, the development of Chi and Alg based biodegradable scaffolds incorporated with silver nanoparticles (AgNPs) with enhanced mechanical properties and biosafe function is proposed. Different ratios of chitosan/alginate (Chi/Alg) were prepared and the effect of different ratio (1:1, 1:2 and 2:1) to the mechanical, biological properties with and without AgNPs and keratinocyte cell growth were investigated. The preliminary result of FTIR, UV-Vis, XRD, FESEM and EDS proved the production of silver nanoparticles. Meanwhile, FTIR, swelling/degradation, DMA, TGA, DSC, FESEM and MTT assay was conducted to study the properties of Chi/Alg based scaffold. FTIR analysis shows the crosslinking of Chi/Alg based scaffold. Swelling/degradation and DMA shows Chi/Alg and chitosan/alginate/silver nanoparticles (Chi/Alg/AgNPs) has adequate swelling and compressive modulus that exceed the epidermis’ Young modulus, thus able to provide mechanical support upon application. Meanwhile, the thermal analysis revealed that the onset decomposition temperature of scaffold were at around 70 ºC which is due to the loss of water present in the scaffold thus thermally safe for soft tissue application. Based on FESEM result, there are different in surface structure of Chi/Alg based scaffold. Finally, with the incorporation of 0.3 % PVP synthesised AgNPs in Chi/Alg based scaffold, cells are able to live up to 14 days. As a result, Chi incorporation in the Alg and AgNPs improved physical, mechanical properties of hydrogel itself and provide biosafe environment during the study.